Learning Strategies in Elementary Schools During the Covid 19 Pandemic - Nur Adinda Putri; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this research is about various aspects in it, including methods, processes, strategies and learning breakthroughs during a pandemic. In the process of this research using descriptive qualitative research methods and data collection techniques with interviews, observations and photos when the research process is carried out. This study aims to reveal the methods used in learning and conclude how the learning strategies during the pandemic in elementary schools. Like schools in general, strategies are carried out online using the Google Meet application and sometimes offline in the learning process. In addition, there are breakthroughs in online learning by teachers, there are several challenges in implementing learning strategies. But even so, elementary school teachers continue to carry out the learning process through the google meet application with the hope that students can continue to study even in pandemic conditions. Parents here play an important role in the success of online learning strategies. Because in the learning process parents do not monitor or accompany their children, so they may not pay attention, so when the teacher gives homework, they cannot answer it. If students cannot answer the questions that have been given, then the learning objectives still cannot be achieved. Because there are students who still do not understand the material presented. This strategy is carried out to prevent and break the spread of the Covid-19 virus that is currently in Indonesia.